Analysis and Evaluation of File Storage and Back Up of Disaster Risk in Diskominfo Data Center - Radian Adi Pratama; Endang Amalia (School of Industrial and System Engineering, Telkom University, 2020)
Disaster is a very damaging and unpredictable event when it happens, threatening the facilities of computersystems and the environment, such as telecommunications systems and data storage. According to theNational Disaster Management Agency (BNPB) Indonesia is very vulnerable to disasters because of thegeographical characteristics. Indonesia current position is between three active plates and a ring of fire.Indonesia's reputation as a disaster-prone country is also noted in the report of The Atlas of the HumanPlanet 2017. The data shows that the threat of natural disasters has doubled in the last 40 years, in line withthe population growth. Diskominfo West Java is an agency that is tasked with carrying out regionalgovernment affairs in West Java in the field of communication and information technology based on theprinciples of autonomy, deconcentrating and co-administration. Diskomifo has a data center that is usefulfor the benefit of the information itself and the Regional Work Unit (SKPD) of the West Java provincialgovernment. A data center must be designed as best as possible to avoid disruption due to disasters,disturbances or errors that can cause damage to the data center itself, therefore it must be avoided orminimized from the impact of the risks that occur and guarantee the availability of the organization'sbusiness continuity if interference or disaster is occurred. In this study, an analysis was carried out relatedto the assessment of risk occurrence, to determine the level of the threats. In addition, in this document abusiness impact analysis is also carried out to determine the priorities of the information system owned bythe organization, so that the organization can prioritize which information system is in the top prioritywhen disruptions occurred.